An overlapping genetic code for frameshifted overlapping genes in Drosophila mitochondria: Antisense antitermination tRNAs UAR insert serine. - Seligmann, H. (Journal of Theoretical Biology, 2012)
Mitochondrial Drosophila genomes possess at least one antisense antiterminator (suppressor) tRNA matching stop codons UAR: antitermination might enable translation after ribosomal frameshift. Proteins translated from samestrand frameshifted and antisense sequences match 26 Genbank proteins (16 are samestrand). Natural frameshifted sequences match more Genbank proteins than after randomizing synonymous codons, suggesting optimization for overlap coding, but some genes avoid overlap coding. Alignments reassign serine to UAR: translational activity by antitermination tRNAs defines a new, presumably stopless overlapping genetic code. Cloverleaf formation by antisense suppressor tRNAs UAA and UAG coevolve with overlapping samestrand and antisense genes, respectively. Coevolution between suppressor tRNAs and sense as well as antisense overlapping genes increases with relative abundances of corresponding sense and antisense (m)RNAs, strong functional evidence for this parallel coding system. Antisense tRNA abundances converge with computed adaptations of antisense tRNAs for translation. Some short frameshifted coding regions are apparently programmed frameshifts putatively producing altered forms of the known main frame protein; most overlapping genes apparently code for unknown proteins. Overlap coding increases gene density without increasing genome size, but decreases with genome size. Parallel genetic systems coded by an additional mitochondrial genetic code in Drosophila confirm similar phenomena in primate mitochondria.